Insecticidal Properties of Ocimum basilicum and Cymbopogon winterianus against Acanthoscelides obtectus, Insect Pest of the Common Bean (Phaseolus vulgaris, L.) - Álvaro Rodríguez-González; Samuel Álvarez-García; Óscar González-López; Franceli Da Silva; Pedro A. Casquero (Insects, 2019)
The bean weevil, Acanthoscelides obtectus Say (Coleoptera: Chrysomelidae: Bruchinae), causes severe post-harvest losses in the common bean, Phaseolus vulgaris L. The control of this insect is still poor and involves the use of conventional insecticides. There is an increasing demand in the search for new active substances and products for pest control towards reduction of adverse effects on human health and the environment. The protection of grains with alternative products, such as essential oils, is a possible alternative to meet the needs described above. Therefore, this investigation evaluated the applications of basil, Ocimum basilicum, and citronella, Cymbopogon winterianus, essential oils for A. obtectus control. These essential oils significantly reduced the bean weight losses and the number of beans damaged by A. obtectus at higher doses than 60 or 120 μL/sample. The number of holes per bean did not differ between the doses of basil essential oil, not even at the dose of 60 μL, while it was higher at 120 μL, probably due to a lower capacity of movement of the insects treated with this dose and/or the oil’s direct or indirect effects on the insects. Basil and citronella oils exhibited similar patterns of insecticidal activity over the insect, both directly in adult insects or indirectly over bean seeds. These essential oils affected the development of A. obtectus since the greatest doses applied on beans decreased the emergence of the bean weevil. The results prove the insecticidal capacity of the tested essential oils and hence their potential as active substances against A. obtectus in environmentally low risk pest control strategies. Supplementary trials should be conducted under real storage conditions.